8+(-5)-(+8)-(-5)=
-23+(-25)-(-23)+(+13)=
-15-(-26)+4-26+24=
[-(-4)-(-10)+(-16)]-(50-13)=
(-45):(-3)-(-11)*3=
(-20)3 do potęgi+(-8):(-1)-(-35):(-7)=
[63:(-9)+(-13)]*(-8)=
niewiadoma:
7- =12 -140+ =-300 17- =-34
a-(-4)=10 b-(-20)=-150 b*(-12)=600
d*(-5)=-70 f:(-4)=-130 600:g=-4
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
8+(-5)-(+8)-(-5)=0
-23+(-25)-(-23)+(+13)=(-12)
-15-(-26)+4-26+24=13
[-(-4)-(-10)+(-16)]-(50-13)=(-7)
(-45):(-3)-(-11)*3=48
(-20)3 do potęgi+(-8):(-1)-(-35):(-7)=(-7997)
[63:(-9)+(-13)]*(-8)=160
7- =12 będzie (-5)
-140+ =-300 będzie (-160)
17- =-34 będzie 51
a-(-4)=10 będzie 6
b-(-20)=-150 będzie (-170)
b*(-12)=600 będzie (-50)
d*(-5)=-70 będzie 14
f:(-4)=-130 będzie 520
600:g=-4 będzie (-150)
:) rozwiązane
zad.1
8 + (-5) + (-8) - (-5)= 8- 5 - 8 + 5 = 13 -13 = 0
-23 + (-25) -(-23) +13 = -23 - 25 +23 +13 = -12
zad.2
- 15 -(-26) + 4 - 26 +24 = -15 + 26 +28-26 = 28 - 15 = 13
[-(-4) - (-10) +(-16)]-(50-13) = 4+10-16-50-13 = -79+14 = -65
(-45):(-3)-(-11)*3 = 15+33 = 48
(-20)3*3 + (-8):(-1)-(-35):(-7) = -180+8-5 =-183
[63:(-9)+(-13)]*(-8) = -20 * (-8) = -160
niewiadoma
7-19 = 12
a-(-4)=10 a=6
d*(-5)=70 d= -14
-140+440=300
f:(-4)=130 f= -520
17-51=-34
b*(-12)=600 b=-50
600:g=4 g=150